Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia) (2013)
The Entomology Museum of the University of Valle (MUSENUV) holds a collection of adult (male and female) Anacroneuria (Plecoptera) specimens which currently represents 75,4% of the known species richness of Colombia (61). In order to expand the knowledge about biodiversity and distribution of this genus in Colombia and the Neotropics, we conducted a review of the specimens deposited in the MUSENUV, in Cali. The specimens correspond to different studies conducted between 1991 and 2011. Field collection of adult individuals (male and female) using two white/black light traps, operated between 18:00 and 21:00 hours accounted for 97% of the collection events. The remaining percentage was obtained by direct collection, using entomological nets either by sampling riparian vegetation or capturing insects at daylight flight. Specimens belong to13 departments, 53 municipalities and about 120 locations, primarily located in the upper and middle Cauca River drainage, from an altitude range between 10 and 3100 m a.s.l. The Andean region was the best represented followed by the Pacific, Caribbean and Amazon regions. There is a gap of information from the Orinoco region. The present data have a great value because provide adequate regional biodiversity assessment, which is crucial to establish environmental diagnostic and conservation strategies.